SOLUTIONS TO IMPROVE CUSTOMER SATISFACTION AT SONY SERVICE CENTER IN NORTHERN VIETNAM - Luong, Thi Hue (Khoa Quốc tế, ĐHQGHN, 2019)
This thesis will discuss and analyze the factors that influence the customer’s level of satisfaction and assist the company to analyze the current situation and identify any existing problems with their services. Data used in this thesis are collected from conducting survey of customer in Ha Noi. With the help from the Manager and staffs of Sony Service Center, the collected data has 236 valid responses, the customer identified 6 components include Responsiveness, Reliability, Tangible, Empathy, Infrastructure and Assurance. Furthermore, the thesis measures consumer satisfaction and identify important strengths need to be retained and weaknesses need to be worked on fast. Based on the result, the thesis also gives some suggestions for Sony Center to further improve Customer Service level.